El Manual Escolar: Pedagogía y Formas Narrativas. - Quiceno Castrillón, Humberto (Revista Educación y Pedagogía, 2010)
EL MANUAL ESCOLAR: PEDAGOGÍA Y FORMAS NARRATIVAS En THE In this article three moments of teaching are analyzed; the appearance of the manual as a technical writing instrument which simplifies or reduces doctrines; the manual as a mechanical art, a method of methods; and the manual as a school textbook, a text among other texts, whose concern is not representing a doctrine or a method anymore, hut education in general. wBBm LE MANUEL SCOLAIRE: PÉDAGOGIE ET PARCOURS NARRATIFS Nous présentons dans ce travail une analyse de trois moments de l’enseignement: la surgie du manuel scolaire comme instrument technique d’écriture qui simplifie ou réduit les doctrines; le manuel en tant qu’art méchanique, méthodes de méthodes el le manuel, texte scolaire, texte parmi d’autres textes dont la préoecupation n’est plus celle de représenter une doctrine ou une méthodc mais l’éducation en general. ¡ Manuales escolares, enseñanza QUICENO, este artículo se analizan tres momentos de la enseñanza: la aparición del manual como instrumento técnico de escritura que simplifica o reduce las doctrinas; el manual como arte mecánico, método de métodos, y el manual como texto escolar, texto entre otros textos, cuya preocupación ya no es representar una doctrina o un método, sino la educación en general. SCHOOL MANUAL: PEDAGOGY AND NARRATIVE WAYS